Postnatal foot length measurement as a proxy to identify low birth weight for frontline health workers in rural Sindh Province, Pakistan: a diagnostic accuracy study - Nick Brown; Andreas Mårtensson; Sarah Saleem; Thomas Mårtensson; Shiyam Sunder Tikmani; Alijaan Inayat Ali (BMJ Open)
Objective To assess the diagnostic accuracy of postnatal foot length (FL) measurements as a proxy to identify low birth weight (LBW) for frontline healthcare workers in rural Sindh Province, Pakistan.Design A community-based cross-sectional study.Setting This study was conducted in the catchment area of Global Network’s Maternal and Newborn Health Registry, Thatta, Sindh Province, Pakistan, from January to June 2023.Participants Singleton live births irrespective of gestational age at birth.Reference standard Birth weight was measured using calibrated digital weighing scales in grams based on the average of three readings with minimal clothing.Index test FL was measured within 48 hours of birth using a rigid transparent plastic ruler in centimetres based on the average of three measurements.Primary outcome Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), receiver operating characteristics curve and area under the curve with 95% CI were calculated. Euclidean distance was used to identify the cutoff of FL to identify LBW. A simple linear equation was created to predict the birth weight.Results Out of 336 analysed newborns, 179 (53.3%) were male and 157 (46.7%) were female. The median birth weight was 2801 g (IQR: 2465–3057), of whom 88 (26.2%) were LBW. The median foot length was 7.9 cm (IQR: 7.6–8.1). For identifying LBW, the foot length cutoff was ≤7.6 cm with 90.3% sensitivity, 81.8% specificity, 63.8% PPV and 96.0% NPV. A FL of 7.6 cm predicted birth weight of 2459.4 g.Conclusion Postnatal FL cutoff of ≤7.6 cm has adequate predictive value served as a simple, low-cost and reliable method to identify LBW for frontline healthcare providers in the rural settings of Thatta without calibrated weighing scales to triage LBW newborns in need of higher-level care.Trial registration number NCT05515211.